The simple geometry of perfect information games - Stefano Demichelis; Klaus Ritzberger; Jeroen M. Swinkels (Institute for Advanced Studies (IHS), 2002)
Perfect information games have a particularly simple structure of equilibria in the associated normal form. For generic such games each of the finitely many connected components of Nash equilibria is contractible. For every perfect information game there is a unique connected and contractible component of subgame perfect equilibria. Finally, the graph of the subgame perfect equilibrium correspondence, after a very mild deformation, looks like the space of perfect information extensive form games.
Keywords: C72; 330; perfect information; subgame perfection; equilibrium correspondence; Spieltheorie; Vollkommene Information; Theorie; Gleichgewicht